Experimental Study on Mechanical Performance of Recycled Fine Aggregate Concrete Reinforced With Discarded Carbon Fibers - Zaid, Osama; Zamir Hashmi, Syed Roshan (Frontiers in Materials, 2021)
With the development of technology in every field, it is necessary to recommend an eco-friendly material to be utilized in the construction industry. Recently, using waste/recycled materials in the concrete as a substitute is a trend to bring sustainability to the construction industry, but the recycled/waste materials has poor mechanical properties, thus to enhance these poor properties, this research studies the mechanical performance of sustainable concrete incorporating waste materials as aggregates, the study is performed in the three stages. In the 1st stage, the natural sand was substituted with recycled sand in the percentage of 0, 35, 70, and 100%, and all the tests i.e. compressive strength, split tensile strength and flexural strength were performed on concrete which was cured in water for 28 days. As the 35% substitution of natural sand with recycled fine aggregate presented the optimum mechanical performance, it was selected for the 3rd stage of the research. In the 2nd and the 3rd stages, the discarded carbon fibers were utilized in concrete with 2%, 4%, and 6% by weight. A total of 90 samples were prepared for this research, in which 30 samples were cubes, 30 samples were cylinders and 30 samples were beams, all the samples were tested at 28 days. Comparative analysis was performed to validate and verify the results of this paper with the relevant literature. The SEM test was also performed on a fractured concrete surface to study its microstructure. The outcome of tests revealed that the utilization of discarded carbon fibers in concrete enhances compressive, split tensile and flexural strength by 27.8%, 17.8%, and 35.9% and acts as a crack bridging and also restrain the propagation of the first cracks. Fibers also helped the concrete to improve its energy absorption capacity and ductility.